Analysis of Forces Applied During Transalveolar Sinus Lift: A Preliminary Clinical Study. Issue 6 (December 2018) - Tavelli, Lorenzo; Borgonovo, Andrea Enrico; Ravidà, Andrea; Saleh, Muhammad H. A.; Zappa, Emanuele; Testori, Tiziano; Wang, Hom-Lay
Abstract : Purpose: To introduce a novel modality that enables the measurement of forces applied during a transalveolar sinus floor elevation (tSFE) and to investigate the influence of anatomical and surgical factors on the necessitated force in sinus membrane detachment. Material and Methods: A new endosinus probe, innovated with a calibrated load cell, was used to test the forces needed to perforate ten maxillary sinuses in 5 human cadavers. The same probe was also used to detach the Schneiderian membrane from the bony floor of 21 human subjects undergoing tSFE. Results: The force needed to cause membrane perforation in the cadaver sample was on average 3.46 ± 1.04 N. The maximum force applied in vivo to a sinus membrane without perforation was 2.01 ± 0.67 N on average. Regression analysis showed that smoking ( P < 0.001), as well as 3.0 mm osteotomy ( P < 0.001), was significantly correlated to increased forces during membrane detachment. Conclusions: The maximum force needed to detach the membrane was found to be, on average, lower than the membrane breaking load in cadavers. Furthermore, because of smoking and a 3.0-mm osteotomy diameter demonstrating a high association with increased forces during membrane detachment, they may be considered as risk factors of membrane perforation.